2005
DOI: 10.1124/mol.105.012518
|View full text |Cite
|
Sign up to set email alerts
|

Gallotannin Inhibits the Expression of Chemokines and Inflammatory Cytokines in A549 Cells

Abstract: Tannins are plant-derived water-soluble polyphenols with wideranging biological activities. The mechanisms underlying the anti-inflammatory effect of tannins are not fully understood and may be the result of inhibition of poly(ADP-ribose) (PAR) glycohydrolase (PARG), the main catabolic enzyme of PAR metabolism. Therefore, we set out to investigate the mechanism of the anti-inflammatory effect of gallotannin (GT) in A549 cells with special regard to the role of poly(ADP-ribosyl)ation. Using an inflammation-focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 48 publications
3
75
2
Order By: Relevance
“…Day zero on the graph is day 7 after tumor injection. *Denotes significant differences (p < 0.05) with respect to control (days [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], † significant with respect to prevention group at day 14. (B) Real time pCR analysis of TNFα, IL-1α and IL6 in the tumor tissue sections of control and GT-treated mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Day zero on the graph is day 7 after tumor injection. *Denotes significant differences (p < 0.05) with respect to control (days [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], † significant with respect to prevention group at day 14. (B) Real time pCR analysis of TNFα, IL-1α and IL6 in the tumor tissue sections of control and GT-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…17 In the nucleus, NFκB binds DNA thus enhancing the transcription of various gene products that regulate proliferation, apoptosis, angiogenesis, invasion, inflammation and metastasis. 18 Since GT was found to inhibit NFκB mediated transcription in lung epithelial cells, 19 we postulated that the anti-colon cancer properties of GT may be through the regulation of the NFκB pathway. GT effects on NFκB activation and regulated gene expression was studied in the two human colon cancer cell lines, HCT-116 (p53 +/+ ) and HT-29 (p53 +/-).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Many studies 41 have shown that NF-kB have a very important role in invasion and metastasis of colon carcinoma through Group iMVD upregulating of MMP-2, MMP-9 expressions. Beside, it was found that inhibiting PARP could also downregulate NF-kB activity, and further downregulate NF-kB-dependent gene expressions.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory effects of PARP have been documented in several in vivo and in vitro studies; 33,34,36 however, data on PARP inhibition in endothelial cells are just emerging. We selectively inhibited PARP in brain endothelium and showed that monocyte adhesion to TNFα-stimulated BMVEC and migration across BMVEC monolayers were attenuated by PARP inhibition (Figure 3).…”
Section: Discussionmentioning
confidence: 99%